Peran Komunikasi Orangtua Dan Anak Meningkatkan Motivasi Belajar Mahasiswa Luar Jawa Di STIKOSA AWS - Alfian Juniar; Jokhanan Kristiyono (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This research is entitled: "ROLE OF COMMUNICATION BETWEEN CHILDREN AND PARENTS IN INCREASING LEARNING MOTIVATION (STUDY OF STUDENTS OUTSIDE OF JAVA ISLAND IN STIKOSA AWS". because they live in the same house. But it is different with parents and children who do not live together or live far apart due to differences in distance and place. Communication is carried out using media such as the Whatsapp video call, voice note, and call applications that do not communicate face-to-face. the author uses descriptive data in the form of data collected in the form of words, pictures, and not numbers. The data collection technique uses observation, interviews and documentation, then uses technical data analysis. So that it can find out how the role, interpersonal communication, learning motivation on students outside Java island d i Stikosa-AWS The author's results found that students from outside Java in Stikosa-AWS communicated with their parents through Whatsapp applications such as video calls, voice notes, and calls. Communication carried out by children and parents is not good because they only rely on the Whatsapp application without making face-to-face meetings and the communication that is established is limited.